2021
DOI: 10.3389/fphar.2021.720776
|View full text |Cite
|
Sign up to set email alerts
|

Common Immune-Related Adverse Events of Immune Checkpoint Inhibitors in the Gastrointestinal System: A Study Based on the US Food and Drug Administration Adverse Event Reporting System

Abstract: Immune checkpoint inhibitors (ICIs) have revolutionized cancer treatment; however, immune-related adverse events (irAEs) in the gastrointestinal (GI) system commonly occur. In this study, data were obtained from the US Food and Drug Administration adverse event reporting system between July 2014 and December 2020. Colitis, hepatobiliary disorders, and pancreatitis were identified as irAEs in our study. Reporting odds ratio (ROR) with information components (IC) was adopted for disproportionate analysis. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Moreover, patients with pancreatitis induced by anti-PD-L1 were less exposed to concomitant drugs at risk of causing pancreatitis. However, the association between different ICIs and pancreatitis remains controversial, as some other studies have demonstrated that both anti-CTLA4 alone and combination treatments with nivolumab and ipilimumab are associated with a higher incidence of pancreatitis than anti-PD-1/PD-L1 alone (Su et al, 2018;George et al, 2019;Bai et al, 2021). Consequently, prospective studies are warranted to further investigate and ascertain the true association between pancreatitis and different ICIs treatments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, patients with pancreatitis induced by anti-PD-L1 were less exposed to concomitant drugs at risk of causing pancreatitis. However, the association between different ICIs and pancreatitis remains controversial, as some other studies have demonstrated that both anti-CTLA4 alone and combination treatments with nivolumab and ipilimumab are associated with a higher incidence of pancreatitis than anti-PD-1/PD-L1 alone (Su et al, 2018;George et al, 2019;Bai et al, 2021). Consequently, prospective studies are warranted to further investigate and ascertain the true association between pancreatitis and different ICIs treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from a meta-analysis showed that the incidence of ICIPI was 0.9-3% for anti-CTLA-4 monotherapy, 0.5-1.6% for anti-PD-1 monotherapy, and 1.2-2.1% for combination therapy of anti-CTLA-4 and anti-PD-1 (Su et al, 2018). Some pharmacovigilance studies generally describe ICIrelated AEs in the gastrointestinal system, including pancreatitis (Reese et al, 2020;Bai et al, 2021). However, knowledge is still scarce about the detailed safety profile of pancreatic AEs following various ICIs in real-world clinical practice as no pancreatic AEs other than pancreatitis and autoimmune pancreatitis is included in the existing pharmacovigilance studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If combined with thrombolytic therapy, immunomodulation can minimize ischemic injury and immune deficiency, thereby preventing systemic infection and improving survival and the long-term prognosis after ischemic cerebral infarction. However, the occurrence of Immune-Related Adverse Events (irAEs) cannot be ignored ( Bai et al, 2021 ; Verheijden et al, 2023 ). Common side effects include non-response of the skin, secondary infection of the nervous system, interstitial pneumonia, enteritis, hepatitis, thyroiditis, etc., which can affect almost all organ systems.…”
Section: The Immunotherapy In Ischemic Strokementioning
confidence: 99%
“…ipilimumab). Whilst the incidence of adverse effects may be considered low (1-30%, depending on the agent and organ system), the impact is a rapid deterioration of function and increased risk of mortality (Bai X et al, 2021). Understanding the risk factors with each compound class is necessary to minimize these risks, particularly considering the increasing trend towards polytherapy.…”
mentioning
confidence: 99%